Pluralism and Justice in Indonesian Inheritance Law: A Comparative Analysis of Customary, Islamic, and Civil Systems - Abdul Ali Mutammima Amar Alhaq; Winarni; Muh. Mutawali; Nuruddin; Zein, Anwar (KALOSARA: Family Law Review, 2025)
The pluralism of inheritance law in Indonesia, encompassing customary law, Islamic law, and the Civil Code, reflects the country’s cultural, religious, and legal diversity. Despite accommodating such diversity, overlapping norms, divergent distribution principles, gender biases, and legal uncertainty remain significant challenges. Limited integrated comparative studies that analyze these three inheritance systems, considering gender and local cultural values, constitute a research gap. This study aims to: (1) conduct a normative-comparative analysis of principles, norms, and inheritance distribution mechanisms across the three legal regimes; (2) evaluate the implications of pluralism for equal rights, legal certainty, and potential disputes through statutory regulations, court decisions, and academic literature; and (3) propose a harmonization model that is inclusive, culturally sensitive, and grounded in substantive justice and gender equality. The study analyzes legislation, documented customary law, and relevant court decisions using a normative juridical and comparative approach. Theoretical frameworks include Legal Pluralism (Griffiths), Substantive Justice (Rawls), and Legal Harmonization (Otto). Findings indicate that, without harmonization, pluralism exacerbates legal uncertainty and gender inequality. A model based on local values and gender equality effectively reduces disputes and strengthens legal certainty, implying the need for national policies with technical guidelines for inclusive, culturally sensitive inheritance law harmonization that safeguards all citizens’ rights.   Keywords: Civil System, Customary System, Inheritance Law, Islamic System The pluralism of inheritance law in Indonesia, encompassing customary law, Islamic law, and the Civil Code, reflects the country’s cultural, religious, and legal diversity. Despite accommodating such diversity, overlapping norms, divergent distribution principles, gender biases, and legal uncertainty remain significant challenges. Limited integrated comparative studies that analyze these three inheritance systems, considering gender and local cultural values, constitute a research gap. This study aims to: (1) conduct a normative-comparative analysis of principles, norms, and inheritance distribution mechanisms across the three legal regimes; (2) evaluate the implications of pluralism for equal rights, legal certainty, and potential disputes through statutory regulations, court decisions, and academic literature; and (3) propose a harmonization model that is inclusive, culturally sensitive, and grounded in substantive justice and gender equality. The study analyzes legislation, documented customary law, and relevant court decisions using a normative juridical and comparative approach. Theoretical frameworks include Legal Pluralism (Griffiths), Substantive Justice (Rawls), and Legal Harmonization (Otto). Findings indicate that, without harmonization, pluralism exacerbates legal uncertainty and gender inequality. A model based on local values and gender equality effectively reduces disputes and strengthens legal certainty, implying the need for national policies with technical guidelines for inclusive, culturally sensitive inheritance law harmonization that safeguards all citizens’ rights.   Keywords: Civil System, Customary System, Inheritance Law, Islamic System